A utilização do marketing de conteúdo e do storytelling como ferramentas para construção de marcas na pós-modernidade - Motta, Alfredo Guimarães (2016)
This study has aimed to develop a framework to support the implementation of content marketing and storytelling for the construction of solid brands in a postmodern world. The motivation behind it has been primarily the importance that brands have for both organizations and individuals, considering its economic role and the satisfaction of objective and subjective needs. Secondly, the size of the investment in brand communication exceeded R$ 120 billion in 2014 in Brazil, recquiring its effective use. Finally, this research is justified by the simultaneous occurrence of two key vectors of change in society: the emergence of a new generation of consumers and the ubiquitous adoption of the internet and mobile telephones by the population that has set a new media paradigm, which demand a review of marketing strategies and tactics for branding. In this context, content marketing and storytelling are marketing tools that have grown in use and in share of the marketing budgets. Assuming that the two techniques can benefit from a more robust set of concepts, parameters and processes to guide their use, an exploratory research was conducted, consisting of fifteen interviews with specialists in brand communications and storytelling, from distinct segments, occupying managerial positions, and in charge of annual marketing budgets equal or superior to R$ 1.000.000. The result of this work is an objective framework to guide the use of content marketing and storytelling for branding, comprehending twelve steps, supported by the experience of industry leaders with significant experience in the disciplines